Does Big Data Analytics Implementation Have a Mediating Role in The Examination of Public Sector Audit Quality? - Nasrudin , Taufik; Firmansyah, Amrie (Politeknik Ganesha Medan, 2024)
This study examines the effect of auditor competence and motivation on audit quality by implementing big data analytics as an intervening variable. The data used in this study comes from a questionnaire survey distributed to respondents during December 2023. The respondents in this study were selected using purposive sampling, with the criteria being auditors at the State Finance Auditorate I BPK. The final sample used in this study was 37 respondents. This study uses the SEM approach with the SmartPLS version 3.0 application to test the data. The findings of this study indicate that competence and motivation have a positive and significant effect on the implementation of big data analytics. In addition, competence has a positive effect on audit quality, but motivation does not affect audit quality. Furthermore, implementing big data analytics does not affect audit quality or mediate the effect of competence and motivation on audit quality. With the results of this study, it is hoped that there will be an increase in training programs, socialization, and the use of big data analytics in audit activities so that it can be useful for improving audit quality.